Manajemen Pemberdayaan Ekonomi Umat melalui Pasar Rakyat Masjid Jami’ Nurul 'Ilmi Semarang - Cassanova, Aulia; Rif’ah, Nihayatur; Kurniawati, Dela (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Masjid Jami' Nurul 'Ilmi Semarang empowers the people's economy by organizing People's Market. This empowerment involves Micro, Small and Medium Enterprises who sell in the mosque yard every Sunday morning. This study aims to explain the strategy of the Masjid Jami' Nurul 'Ilmi’s da'wah management in the community economic empowerment program based on the People's Market. This study is a qualitative study with a field study model and descriptive discussion. The results of the study indicate that the success of da'wah management strategy of community economic empowerment through the People's Market includes; availability of funds, active involvement of participants, progressive drivers, and good cooperation between elements. The factor of availability of funds is in the form of the procurement of the UUP program. The factor of active involvement of participants includes the role of mosque administrators, traders, and the community. Progressive driving factors include management innovation in the form of the Sunday Morning Study program and the procurement of shopping vouchers. The factor of cooperation between elements includes cooperation between mosque administrators, donors, traders, and the surrounding community.